BaCeO3 dopado com 5%Mol Y2O3 : sinterização, microestrutura e condutividade elétrica protônica - Araújo, Huyrá Estevão de (2015)
The development of solid electrolytes for Solid Oxide Fuel Cells is a challenge to enabling this technology as sustanaible energy resource. Ceramics based on Yttrium doped- Barium cerate are potential candidates for this application due high protonic electrical conducitivity at intermediate temperatures, 500~600o C. In this present work, BaCe0,9Y0,1O3 based ceramics were prepared by solid state reaction and wet chemical route, specifically amorphous citrate process. The sintering parameters were controlled by dwell temperature, dwell time and heating rate. X ray diffraction was performed to powders, green and sintered ceramics and the perovskite phase was obtained but it was observed that lattice symmetry shows strongly dependent on dwell sintering and powders preparation route. The scanning electronic microscopy and sintering at dilatometer were performed and have shown a liquid phase sintering. A model to BaCe0,9Y0,1O3 sintering was proposed which the partial substitution of Yttrium atoms at host site of Cerium leads to a liquid phase formation at eutectic point of BaCeO3 composition and this promotes densification. The following step is dedicated to re-incorporation of Yttrium atoms to lattice and returning to conductive phase. The success of this step is favored by higher temperatures and chemical homogeneity of powders. The electrical conductivity shows stronger dependence on sintering profile at wet chemical powder than at solid state reaction powder. Among sintered ceramics with density at least 95% than theoretical density, the higher conductivity was achieved with lower temperature sintering and better chemical homogeneity, with =10-2 S.cm-1 at 500ºC in humidity atmospheres.